Profiles of brain metastases: Prioritization of therapeutic targets. Issue 11 (9th October 2018) - Ferguson, Sherise D.; Zheng, Siyuan; Xiu, Joanne; Zhou, Shouhao; Khasraw, Mustafa; Brastianos, Priscilla K.; Kesari, Santosh; Hu, Jethro; Rudnick, Jeremy; Salacz, Michael E.; Piccioni, David; Huang, Suyun; et al.
Abstract : We sought to compare the tumor profiles of brain metastases from common cancers with those of primary tumors and extracranial metastases in order to identify potential targets and prioritize rational treatment strategies. Tumor samples were collected from both the primary and metastatic sites of nonsmall cell lung cancer, breast cancer and melanoma from patients in locations worldwide, and these were submitted to Caris Life Sciences for tumor multiplatform analysis, including gene sequencing (Sanger and next‐generation sequencing with a targeted 47‐gene panel), protein expression (assayed by immunohistochemistry) and gene amplification (assayed by in situ hybridization). The data analysis considered differential protein expression, gene amplification and mutations among brain metastases, extracranial metastases and primary tumors. The analyzed population included: 16, 999 unmatched primary tumor and/or metastasis samples: 8, 178 nonsmall cell lung cancers (5, 098 primaries; 2, 787 systemic metastases; 293 brain metastases), 7, 064 breast cancers (3, 496 primaries; 3, 469 systemic metastases; 99 brain metastases) and 1, 757 melanomas (660 primaries; 996 systemic metastases; 101 brain metastases). TOP2A expression was increased in brain metastases from all 3 cancers, and brain metastases overexpressed multiple proteins clustering around functions critical to DNA synthesis and repair and implicated in chemotherapy resistance, including RRM1, TS, ERCC1 and TOPO1. cMET was overexpressed in melanoma brain metastases relative to primary skin specimens. Brain metastasis patients may particularly benefit from therapeutic targeting of enzymes associated with DNA synthesis, replication and/or repair. Abstract : What's new? Brain metastases are difficult to treat and generally lethal. Here, the authors sought clues to possible treatment targets by comparing the molecular characteristics of lung, breast, and skin cancers with those of brain metastases. They analyzed DNA sequence, protein expression, and gene amplification on over 17, 000 samples, the largest metastases cohort ever studied. They found that the enzyme TOP2A, involved in DNA transcription, was enriched in the metastatic cells relative to the primary tumor cells. Other enzymes, involved in DNA synthesis, repair, and replication were also overexpressed in metastases, and could potentially be useful therapeutic targets.